AMBULANCE SERVICE TREAT AND REFER GUIDELINES: A QUALITAIVE INVESTIGATION INTO THE USE OF TREAT AND REFER GUIDELINES BY AMBULANCE CLINICIANS. Issue 5 (18th April 2015) - Colver, Keith; Abhyankar, Purva; Niven, Catherine
Abstract : Background: Over the last decade there has been a steadily increasing demand for unscheduled healthcare services, including the ambulance services. To address this demand, various projects have been developed to reduce admissions to the emergency department. One of these was the introduction of Treat and Refer (T&R) guidelines, to allow ambulance clinicians to treat certain groups of patients in the community without the need to convey them to hospital. Aims: This study aims to explore the challenges and barriers faced by ambulance clinicians in the use of T&R guidelines, to inform the future development and governance of non-conveyance guidelines and interventions. Methods: Semi-structured interviews were conducted with 18 ambulance clinicians. Data were analysed using framework analysis. Setting: A national UK NHS ambulance service. Results: There was a broad support for the concept and policy of T&R; however the participants had mixed views with respect to the actual practice of treating and referring patients. Participants acknowledged the potential benefits of T&R for patients and the NHS, but identified several risks in using T&R in routine practice. Their perceptions of risk seemed to determine whether and how the guidelines were used. Challenges in the use of T&R included: lack of training and knowledge, fear of litigation, a lack of support from the management and difficulties in decision-making. Conclusions: This study and the supporting literature do not support the use of T&R guidelines in their current format by traditionally trained ambulance clinicians. Ambulance clinicians have identified the need for further education and support. The conceptual support for T&R may provide a foundation to develop and improve the education and support for ambulance clinicians. This should be combined with implementation/review strategies, clinician-led decision support and management support which can provide the ambulance clinician with the skills and confidence to take responsibility for non-conveyance.